Travestis, territórios e prevenção de AIDS numa cidade do interior de São Paulo - Sabatine, Thiago Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Essa pesquisa busca compreender as ações empreendidas e/ou propostas para a promoção da qualidade de vida e saúde das travestis que se prostituem numa cidade do interior do estado de São Paulo. A investigação baseia-se em etnografia dos territórios e interações no mercado do sexo e em demais vivências cotidianas com as travestis e explora como a prevenção de aids opera disciplinando sujeitos e alargando o campo de direitos a saúde. O estudo analisa os significados atribuídos pelas travestis ao adoecimento e a saúde, o risco a aids, bem como a interação nos espaços institucionais de saúde, com enfoque nos dilemas e potencialidades frente ao reconhecimento das diferenças das travestis e suas necessidades para uma vida qualificada

This research aims to understand the actions undertaken and/or proposed to promote the quality of life and health of transvestites who prostitutes themselves in a country town of São Paulo. The investigation is based on the territories ethnography and interactions in the sex market and in the other daily experiences with the transvestites and it explores how the prevention of AIDS works disciplining the individuals and enlarging the field of health rights.The study analyses the meanings assigned by the transvestites to the illness and health, the risk of AIDS, as well as the interaction in the institutional spaces of health, with emphasis on dilemmas and potentialities facing the recognition of the differences of the transvestites and their needs for a qualified life
Keywords: Travestis - Sexo; Saude; AIDS (Doença); Identidade sexual; Transvestites - Health